Modification of cryoprotectants on sperm cryopreservation: A study of embryo development (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: This research was conducted to analyze the effect of cryopreservation of sperm using modified cryoprotectants on embryo development through in vitro fertilization (IVF). In this research, three types of cryoprotectant combinations were compared, including Nakagata, modified cryoprotectant, and commercial (Kitazato). Materials and Methods: Several parameters, namely sperm concentration, motility, morphology, plasma membrane integrity, cryo-survival rate, and viability rate, were measured and compared before vitrification and warming. Embryo development was also observed on the first and third days of development based on the cell number, cell size, and fragmentation rate. Results: Sperm cryopreservation exhibited a negative influence on embryo quality. Both Nakagata cryoprotectants and modified cryoprotectants attained good-quality embryos. In terms of embryonic development, this research revealed a modified cryoprotectant superior to Nakagata’s cryoprotectant, although Kitazato was superior to the Nakagata cryoprotectant and modified cryoprotectant. Significant differences were found in the three cryoprotectants on observations on day 1 and day 3, all of them with p-value < 0.05. Conclusion: Modified cryoprotectant was found to be better than Nakagata but less significant than Kitazato in terms of embryonic development quality. Therefore, modified cryoprotectants could be a better alternative compared to commercial (Kitazato) cryoprotectants for improving embryo quality.J. Adv. Vet. Anim. Res., 11(3): 554–552, September 2024http://doi.org/10.5455/javar.2024.k804